Pensions can work without economic growth - Laua Wiman (Post-growth Economics Network (PEN), 2025)
This working paper is a tentative, solutions-oriented response to concerns that pensions would not work without economic growth. It aims to concretize post-growth visions, but also validate post-growth thinking to those who consider it too far outside the mainstream. To the contrary, this analysis begins from mainstream policy aims and economic concerns, and as its result proposes institution types that are already widespread. A pension system can be widely acceptable if it promotes three 'provisioning aims': poverty alleviation, income maintenance, and voluntary provisioning. Without economic growth, possible 'adverse economic conditions' of pension systems include low earnings; low, negative, or volatile interest rates; high inflation; and demographic aging. Additionally, even financially sustainable pension funds can have 'adverse social effects'if their interest income is extractive, exploitative, or inequality-amplifying. I argue that three broad institution types could constitute a post-growth pension system: non-contributory (governmentfinanced) minimum/basic pensions, contributory pay-as-you-go pensions, and collective pension funds. Together they promote all three provisioning aims. The provisioning aims make tradeoffs against each other and their institutions have different weaknesses regarding adverse economic conditions and social effects. Still, even without economic growth, most wealthy economies could probably promote at least poverty elimination and income maintenance without paradigmatic reforms. To close, I anticipate four interesting aspects of post-growth pensions governance: benefit protection versus cost control, distribution versus redistribution, challenging of economic individualism, and property rights within funded pension schemes.
Keywords: 330; growth dependence; eco-social policy; sustainable welfare; inequality; financialization; provisioning